Perceptions of emergency medicine residents toward online medical education during the COVID-19 pandemic: a cross-sectional survey study - Turki S. Al-Harbi; Ali Al-Shehri; Thamer K. Zoghbi; Bader W. Abulhamail; Turki Aljuhani (Saudi Journal of Emergency Medicine)
Background: The COVID-19 pandemic affected many aspects of medical education that were based on the traditional classroom experience. To maintain postgraduate education during the lockdown, many of these activities continued via virtual methods. We aim to assess residents' perceptions of online medical education. Methods: This is a cross-sectional study targeting emergency medicine residents in the western region of Saudi Arabia. An electronic self-administered validated survey was used to assess the residents' experiences and perceptions of online medical education. Results: A total of 125 participants were surveyed (52% response rate). There was a significant increase in hours spent in online education after COVID-19 according to Wilcoxon signed rank test (p < 0.001). On a Likert scale, most residents agreed that they found online medical education enjoyable and easy to engage with. However, most did not find it as interactive as the traditional teaching methods. The most enjoyed aspects were the ability to learn in their own homes, and the flexibility in scheduling. The biggest barriers were difficulties in maintaining focus, and technical problems. Most (59.2%) of the residents found that online learning did not cover procedural skills acquired from simulation and direct patient training. Conclusion: The convenience and diversity of online education make it a good alternative tool compared to traditional methods. Despite the disadvantages of online education, we think it will continue to play a role in residency programs going forward in the future. [SJEMed 2023; 4(2.000): 092-098]